Preliminary Study on Ultrasonic Ageing Zhenjiang Vinegar Mechanism Based on Maillard Simulation System - Xiaoke Ma; Tingting Li; Yuanqing He; Min Chen; Jie Zhou; Lijing Yin; Haile Ma (Journal of Food Quality)
In this study, ultrasonic technology was used to treat Zhenjiang vinegar, and the effects on the physicochemical characteristics of Zhenjiang vinegar were investigated. The influences of ultrasound time and power on the number of induced hydroxyl radicals and superoxide radicals were also investigated. Besides, the novel simulation system of the Maillard reaction was built to research the effects of different ultrasonic times and power treatment on Zhenjiang vinegar. The results show that, under the conditions of ultrasonic treatment, the changes of Zhenjiang vinegar physiochemical index, such as color, reducing sugar, and amino acid, are consistent with those of natural ageing. In addition, ultrasound can produce a cavitation effect and cracking water molecules to produce hydroxyl radicals and superoxide radicals, so as to achieve the ageing effect of vinegar.